Coinfection and superinfection in ICU critically ill patients with severe COVID-19 pneumonia and influenza pneumonia: are the pictures different? - Chen, Ziying; Zhan, Qingyuan; Huang, Linna; Wang, Chen (Frontiers in Public Health, 2023)
Background: Similar to influenza, coinfections and superinfections are common and might result in poor prognosis. Our study aimed to compare the characteristics and risks of coinfections and superinfections in severe COVID-19 and influenza virus pneumonia.The data of patients with COVID-19 and influenza admitted to the intensive care unit (ICU) were retrospectively analyzed. The primary outcome was to describe the prevalence and pathogenic distribution of coinfections/ICU-acquired superinfections in the study population. The secondary outcome was to evaluate the independent risk factors for coinfections/ICU-acquired superinfections at ICU admission. Multivariate analysis of survivors and non-survivors was performed to investigate whether coinfections/ICU-acquired superinfections was an independent prognostic factor.In the COVID-19 (n=123) and influenza (n=145) cohorts, the incidence of coinfections/ICU-acquired superinfections was 33.3%/43.9% and 35.2%/52.4%, respectively. The most common bacteria identified in coinfection cases were Enterococcus faecium, Pseudomonas aeruginosa, and Acinetobacter baumannii (COVID-19 cohort) and A, baumannii, P, aeruginosa, and Klebsiella pneumoniae (influenza cohort). A significant higher proportion of coinfection events was sustained by Aspergillus spp [(22/123,) and (18/145, 12.4% in influenza)].The COVID-19 group had more cases of ICU-acquired A, baumannii, Corynebacterium striatum and K, pneumoniae. A, baumannii, P, aeruginosa, and K, pneumoniae were the three most prevalent pathogens in the influenza cases with ICU-acquired superinfections. Patients with APACHE II ≥18, CD8+ T cells ≤90/µL, and 50